Analisis Pengaruh Suhu Terhadap Nilai Konduktivitas Pada Perpindahan Panas Secara Konduksi Menggunakan Virtual Lab Amrita - Saoqibillah, Lutfi; Malik, Adam (Prodi Fisika FKIP Unram, 2024)
This study aims to determine the effect of temperature value on conductivity value (conduction heat rate) in conduction heat transfer. The method used in this research is an experimental method with variable temperature and variable conductivity values of materials using amrita virtual lab simulation software. The variable variation used in this study is the difference in materials using cardboard and glass with variations in voltage, current, diameter and thickness of the same material. The results of this study indicate the effect of temperature on the conductivity value, if the conductivity value of a material is small then the temperature will be large because this experiment was conducted on insulating materials on both objects. Temperature will inhibit heat transfer by conduction, it can be concluded that both materials are good heat insulators. Keywords: Conduction heat transfer, Temperature, vlab Amrita.